Consumer-Based Insights for Indonesian Market Entry Strategy Development of South Korean Food Manufacturing Companies - Andika, Aditya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The interest for Korean food products in Indonesia is growing at a rapid pace. Korean Wave has popularized various aspects of Korean culture in Indonesia, including Korean food. The popularity of Korean food products in Indonesia provides opportunities for South Korean food manufacturing companies that want to enter the Indonesian market. South Korean food manufacturing companies who want to succeed in doing business in Indonesia need to understand the factors that affect Indonesian consumers’ purchase interest of Korean food and insights around market entry strategies that work in Indonesia. This study conducted a literature review and found that there are various factors that affect Indonesian consumers’ purchase interest of Korean food. These factors will be discussed in this study. Based on those factors, this study will develop suggestions and insights that can be used by South Korean food manufacturing companies to develop market entry strategies to enter the Indonesian market.